Implementation of a Lean Manufacturing and SLP-based system for a footwear company - Silvestre, Sergio Enrique Munive (2022)
Paper aims: This research article addresses an innovative solution to face one of the main problems in the footwear industry, namely the high order non-fulfillment rate. Originality: This research offers companies in the footwear industry the possibility of implementing Andon through a structured and planned process that allows expediting problem solving. The advantage of this system is the ability to signal the status of workstations through rapid visual identification. Moreover, in this way social distancing is also secured, in line with World Health Organization guidelines to prevent the spread of COVID-19. Research method: The article presents four phases through which the case study was addressed. Planning (determination of objectives), Restructuring of the Operations Area, Improvement of the Production Line and Continuous Improvement. Main findings: An Arena simulation system was used to establish a new scenario where the defective product indicator decreases by 3.13% and productivity improves by about 38%. In turn, the resulting increase in the number of orders enhances company sales and profits, as well as the ability to meet the customer demand in a timely manner. Implications for theory and practice: The case study suggests that the main causes of this issue (high order non-fulfillment rate) are the increasing rate of defective goods, delays in the production process, and excessive time consumption in the movement of staff and materials. This research serves as the basis for future lines of research, as well as for other organizations with similar characteristics to implement the proposal.